Purification of Curcumin Derivate (1,5-bis(4’-hydroxy-3’-methoxyphenyl)-1,4-pentadien-3-on) Using Chromatotron - Harimurti, Sabtanti; Fadhilah, Alfan; Widada, Hari; Damarwati, Vella Lailli (Universitas Muhammadiyah Surakarta, 2024)
Curcumin derivate with IUPAC name 1,5-bis(4’-hydroxy-3’-methoxyphenyl)-1,4-pentadien-3-on is also known as Gamavuton-0 (GVT-0) reported has an activity as anti-inflammation and anti-cancer. GVT-0 can be synthesized using vanillin and acetone as starting material by aldol condensation. Purification process of GVT-0 after synthesis usually was done using maceration. This method resulting un-pure GVT-0, therefore, another separation technique of Chromatotron was chosen. This research aims to investigate the effectiveness of Chromatotron towards the purity of GVT-0. The study was started by GVT-0 synthesis. The synthesis was using 4.4 mole of vanillin and 1 mole acetone as the raw material. Microwave irradiation was used as the energy source. Isolation of GVT-0 using hot water maceration. Further, the purification of GVT-0 was conducted using Chomatotron. First step of purification using Chomatotron was preparing best ratio between hexane and chloroform as solvent to remove vanillin. Further, the best combination of solvent was used to separate all the vanillin remaining in the bulk of GVT-0. Last step after all vanillin was removed, the GVT-0 remining in the silica was elucidated using chloroform. The purity was evaluated using Melting-point analysis and Thin Layer Chromatography (TLC) with four different mobile phases. Based on the data of melting point and TLC, a pure GVT-0 was obtained. The Chomatotron may be recommended for purification of GVT-0, however this method consumes a lot of organic solvent that may need to be improved in the future with more environmentally process